Qawâ’id al-Tafsîr as an Integrative Methodological Framework: Its Relation to Arabic Language and Uṣûl al-Fiqh: Qawâ’id al-Tafsîr sebagai Kerangka Metodologis Integratif: Relasi dengan Bahasa Arab dan Uṣûl al-Fiqh - Khaerussalam, Ahmad; Rokhim, Abdur (Direktorat Pondok Pesantren Universitas Islam Indonesia, 2026)
The study of qawâ’id al-tafsîr occupies a central position in Qur’anic exegesis as it serves as a methodological framework that ensures consistency, objectivity, and validity in interpreting the Qur’an. This article aims to analyze the concept of qawâ’id al-tafsîr and examine its relationship with the Arabic language and uṣûl al-fiqh as two foundational disciplines of tafsîr methodology. This research employs a qualitative approach through library research by examining classical and contemporary exegetical works, Arabic linguistic literature, and uṣûl al-fiqh sources. The findings reveal that qawâ’id al-tafsîr has a structural connection with the Arabic language, particularly in grammatical, semantic, and rhetorical aspects that determine the accuracy of Qur’anic textual interpretation. Furthermore, its relationship with uṣūl al-fiqh is evident through shared methodological principles, such as ‘âm-khâṣṣ, muṭlaq-muqayyad, and nâsikh-mansûkh, which function to balance textual meaning with the objectives of Islamic law (maqâṣid al-sharî’ah). This article argues that the integration of qawâ’id al-tafsîr, Arabic linguistics, and uṣûl al-fiqh is a prerequisite for constructing a comprehensive and systematic tafsîr methodology that remains relevant to contemporary scholarly challenges. [Kajian qawâ’id al-tafsîr menempati posisi sentral dalam ilmu tafsir karena berfungsi sebagai kerangka metodologis yang menjaga konsistensi, objektivitas, dan validitas penafsiran Al-Qur’an. Artikel ini bertujuan menganalisis konsep qawâ’id al-tafsîr serta mengkaji relasinya dengan bahasa Arab dan uṣûl al-fiqh sebagai dua disiplin yang membentuk fondasi metodologis tafsir. Penelitian ini menggunakan pendekatan kualitatif melalui studi kepustakaan dengan menelaah karya tafsir klasik dan kontemporer, literatur kebahasaan Arab, serta sumber-sumber uṣûl al-fiqh. Hasil kajian menunjukkan bahwa qawâ’id al-tafsîr memiliki keterkaitan struktural dengan bahasa Arab, khususnya dalam aspek gramatika, semantik, dan retorika, yang berperan menentukan ketepatan pemaknaan teks Al-Qur’an. Selain itu, relasinya dengan uṣûl al-fiqh tampak melalui kesamaan prinsip metodologis, seperti ‘âm-khâṣṣ, muṭlaq-muqayyad, dan nâsikh-mansûkh, yang berfungsi menyeimbangkan makna tekstual dengan tujuan hukum Islam (maqâṣid al-sharî’ah). Penelitian ini menegaskan bahwa integrasi qawâ’id al-tafsîr, bahasa Arab, dan uṣûl al-fiqh merupakan prasyarat bagi terbentuknya metodologi tafsir yang komprehensif, sistematis, dan relevan dalam menjawab tantangan keilmuan kontemporer.]